(3efXheI GdTYQGA heRgQ GdCeQGAs
(3ChdgG (B:s
(3jHOC HGdhQbI GdCNjQI ef (B( (3GdHGH GdKGdK hGdYTQjf (B) (3jJdhg HGH GdgLGA s
(3BNQgG (B:s
(3jfJgi HGdHjGf GdChS Hf MLQ ChdgG (B: (3QCjJ jRjOkG HOjfi JTGhS QhjOkG jRjO Effi ef JCed s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B1s
(3GdfSNI HgG MhGTs
(3hgh eLehYI ef GdMce hGdCTYGQ hGdCNHGQs
(3hgh ai YOI CLRGA s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdCOHs